The diagnostic/prognostic roles and biological function of the IFIT family members in acute myeloid leukemia - YiFan Zhao; Yi Zhang; WenYi Lu; Rui Sun; RuiTing Guo; XinPing Cao; Xingzhong Liu; Cuicui Lyu; MingFeng Zhao (BMC, 2023)
Abstract Background The Interferon-induced protein with tetratricopeptide repeat (IFIT) family, IFIT1/2/3/5, play an important role in different tumors progression. However, the prognosis significance and biological role of IFIT family members in acute myeloid leukemia (AML) remains unclear. Methods We obtained the gene expression data and clinical information of 173 AML patients from The Cancer Genome Atlas (TCGA) database. Several databases were used in our study, including GEPIA, MethSurv, STRING, GSCA and GeneMANIA database. Results The mRNA expression of IFIT1/2/3/5 was elevated in AML patients and had a high ability to distinguish AML from controls based on the receiver operating characteristic (ROC) curve (AUC > 0.9). Kaplan-Meier survival analysis showed that higher levels of IFIT2/3/5 expression predict poor prognosis in AML patients. Besides, the DNA methylation analysis suggested that 7 CpG sites of IFIT2, 4 CpG sites of IFIT3 and 10 CpG sites of IFIT5 were significantly associated with the prognosis of AML patients. In addition, IFIT2/3/5 expression was significantly positively associated with the immune cell infiltration and immune checkpoint expression, such as CTLA4, PDCD1, LAG3, and TIGIT. Finally, drug sensitivity analysis revealed that AML patients with high expression of IFIT2/3/5 were resistant to multiple drugs, but sensitive to dasatinib. Conclusion IFIT family genes might serve as biomarkers for diagnosis, prognosis and drug sensitivity in AML patients. The activation or blocking of IFIT-related signaling pathways may provide novel insights into immunotherapy for patients with AML.